The preparation and properties of 1,1-difluorocyclopropane derivatives - Adekenova, Kymbat S.; Wyatt, Peter B.; Adekenov, Sergazy M. (Beilstein Journal of Organic Chemistry, 2021)
Recently, the functionalization of organic molecules with fluorine substituents has grown rapidly due to its applications in such fields as medicine, agriculture or materials sciences. The aim of this article is to review the importance of 1,1-difluorocyclopropane derivatives in synthesis. It will examine the role of the fluorine substituents in both ring-forming and ring-opening reactions, as well as methods for obtaining difluorocyclopropanes as single enantiomers. Several examples are provided to highlight the biological importance of this class of compounds.
Keywords: biological activity; cyclopropanation; difluorocyclopropane derivatives; synthesis